Integration of Matlab and LabVIEW for the Simulation of an AVR in a 1.1 kVA Synchronous Generator - Mulyanto, Widodo Pudji; Leci, Geraldi; Sulistiawati, Irrine Budi (ELKHA : Jurnal Teknik Elektro, 2025)
Automatic Voltage Regulator (AVR) in the system functions to regulate and stabilize the output voltage of the synchronous generator to remain constant, even in the event of load changes or system conditions. This research uses a software-based approach by integrating LabVIEW data acquisition to measure the actual input and output voltages of the generator and to create the transfer function along with its simulation using Matlab. The Automatic Voltage Regulator used is designed for a 1.1 kVA synchronous generator, Delorenzo DL 1026A. Simulation in Simulink is performed to analyze the system response towards changes in the load using PID as the controller. With the auto-tuned values of Kp = 1.815, Ki = 288.290, and Kd = 0, the system maintained voltage stability under disturbances of 0.1 pu, 0.25 pu, and 0.5 pu. The developed AVR was able to respond to load changes quickly and maintain the stability of the generator"™s output voltage by showing relatively small steady-state error indicated with steady state conditions for 0.00018 pu, 0.00024 pu, and 0.00033 pu in every load change. This phenomenon proves the PID controller resulting from the proposed method is capable of maintaining the voltage magnitude according to the load changes that occur. This research is expected to serve as a basis development of a more reliable and adaptive voltage control system for small-scale generators.